Facade Morphology with Kinetic System in Tall Buildings - Dharmatanna, Stephanus Wirawan (Institut Teknologi Adhi Tama Surabaya, 2024)
The urban population's dependence on natural resources to fulfill their daily energy needs is increasingly leading the earth to experience an energy crisis. One of the efforts that can be made to save the earth is to provide replacement energy. The solution to the energy crisis can be realized through architectural designs that care for nature by focusing on renewable natural resources. One form of implementation is by processing wind power into energy. The facade as the outermost surface of a tall building, has the potential to process wind power into energy because it receives the wind directly. Kinetic systems can be applied to the facade so that it can process the wind power available in the environment more effectively. This research aims to examine kinetic facade models from several architectural works that use kinetic design concepts and approach the average wind speed of Surabaya City. This research uses the methods of precedent study and comparative study. The result of this research is the discovery of hanging and rotational kinetic facade forms.